New Exact Solutions of Landau-Ginzburg-Higgs Equation Using Power Index Method. (12th January 2023) - Ahmad, Khalil; Bibi, Khudija; Arif, Muhammad Shoaib; Abodayeh, Kamaleldin
Abstract : In the present study, the optimality approach is applied to find the exact solution of the Landau-Ginzburg-Higgs Equation (LGHE) using new transformations. This method is a direct algebraic method for obtaining exact solutions of nonlinear differential equations. We find suitable solutions of the LGHE in terms of elliptic Jacobi functions by applying transformations of basic functions. Exact solutions of the equations are obtained with the help of symbolic software (Maple) which allows the computation of equations with parameter constants. It is exposed that PIM is influential, suitable, and shortest and offers an exact solution of LGHE.